Efeitos do extrato bruto da cianobactéria Radiocystis fernandoi no teleósteo, Hoplias malabaricus - Paulino, Marcelo Gustavo (Universidade Federal de São Carlos, 2015)
Eutrophication of the aquatic environment favors cyanobacteria blooms and affects the biota due to organoleptic water changing and the release of toxins. The objective of this study was to evaluate the effect of microcystin contained in the crude extract of the cyanobacteria Radiocystis fernandoi (R28 strain) in the fish Hoplias malabaricus assessing the degree of structural and functional impairment of the liver, the accumulation potential in muscle and risk to human health. Traíras were injected intraperitoneally with 100 μg MC-LReq kg-1 following two experimental protocols: (i) acute exposure with the application of a single dose of the crude extract and evaluation after 12 and 96 hours and (II) chronic exposure in which a dose was injected every 72 hours during 30 days. Genotoxic, biochemical, physiological and morphological biomarkers were used to evaluate the action of toxins, structural and ultrastructural damage in the liver, the detoxification mechanisms and changes in energy metabolism. The R28 strain produced mainly the MC-RR and MC-YR showing hepatotoxic potential. In the liver there was accumulation of MC-YR after acute and chronic exposure and MC-RR and MC-RR only after chronic exposure. There was not MC accumulation in muscle. The accumulation of the variants (MC-RR and MC-YR) depends on the concentration and the body's defense system for depuration and biomagnification. Acute and chronic exposure caused inhibition of the serine protein phosphatase / threonine type of PP2A activity, increased alanine aminotransferase and aspartate activity and direct bilirubin in plasma indicating liver damage. Macroscopically occurred changes in the color, texture and liver mass; microscopically the morphology of hepatocytes and intracellular organelles were altered and there were dilated sinusoids and hyperemia. After 30 days, the frequency of changes increase, and fibrous tissue disrupted the architecture of hepatic tissue. Changes in intermediary metabolism as glucose, liver glycogen, pyruvate and lactate showed increased energy demand and physiological stress. Moreover, there was activation of phase I of the biotransformation system and alterations in cellular antioxidant systems. Morphological signs of recovery in the liver were observed after 96 hours (single dose) to MC, but not after 30 days and no signs of cell regeneration. DNA damage were observed as well. The biochemical changes and liver structure showed functional impairment of the liver. In conclusion, the microcystin present in the crude extract of cyanobacteria R. fernandoi (R28 strain) combined with other substances in the extract may compromise the health and survival of the animal.
Keywords: Peixe - fisiologia; Microcistina; Marcadores biológicos; Bioacumulação; Danos hepáticos; Cianobactéria; Microcystins; Biomarkers; Stress-oxidative; Bioaccumulation; Liver damage; Cyanobacteria; CIENCIAS BIOLOGICAS::FISIOLOGIA